COVID-19 Mobility Policies Impacts: How Credible Are Difference-in-Differences Estimates? - Joakim A. Weill; Matthieu Stigler; Olivier Deschenes; Michael R. Springborn (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic brought unprecedented policy responses and a large literature evaluating their impacts. This paper re-examines and add to the evidence on the impact of COVID-19 mobility-restricting policies on mobility indicators. We first find that two-way fixed effects estimates are not robust to minor specification changes, where the same policy can be found to significantly increase or decrease mobility, depending on the specification. Therefore, due to the large number of researcher's degrees-of-exibility, researchers can focus on a set of results that appears stable, while ignoring problematic ones. Further, recently developed heterogeneity-robust difference-in-differences methods only partially mitigate these issues.
Keywords: I12; I18; C18; C23; H75; 330; COVID-19; social distancing; mobility; difference-in-differences; researcher degrees-of-flexibility; mobility-restricting policies